2016
DOI: 10.1007/s10620-016-4272-5
|View full text |Cite
|
Sign up to set email alerts
|

Domperidone to Treat Symptoms of Gastroparesis: Benefits and Side Effects from a Large Single-Center Cohort

Abstract: In this large single-center study of patients treated with domperidone, side effects necessitating discontinuing treatment occurred in 12 %. The majority of patients remaining on treatment experienced an improvement in symptoms of gastroparesis, particularly postprandial fullness, nausea, vomiting, and stomach fullness. Thus, domperidone treatment is beneficial for many patients with symptoms of gastroparesis. This study provides needed benefit and risk information concerning treating patients with domperidone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 27 publications
2
47
0
4
Order By: Relevance
“…Other studies have shown improvement in gastroparesis symptoms with domperidone therapy . Symptoms that have been reported as improving include nausea, vomiting, postprandial fullness, and early satiety.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Other studies have shown improvement in gastroparesis symptoms with domperidone therapy . Symptoms that have been reported as improving include nausea, vomiting, postprandial fullness, and early satiety.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have shown improvement in gastroparesis symptoms with domperidone therapy. 7,8,17,18 Symptoms that have been reported as improving include nausea, vomiting, postprandial fullness, and early satiety. The findings of this study largely agree with those studies, with the exception of vomiting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metoclopramide and domperidone, a D2 dopamine receptor antagonist, are the most widely used drugs, but only metoclopramide is currently approved by the Food and Drug Administration (FDA) in the United States. This treatment has limited efficacy and carries a black-box warning for tardive dyskinesia [29,30]. This makes management more challenging, and patients frequently present with severe symptoms due to either progression of the disease or medications losing efficacy over time, turning the disease refractory to medical treatment [31].…”
Section: Summary Of Evidencementioning
confidence: 99%